2009
DOI: 10.1016/s2255-4971(15)30165-8
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Varusing for Osteoarthritis of Valgus Knee: A Long-Term Follow-Up

Abstract: Objective: Assess the long-term results of distal femoral varusing osteotomy and try to establish predictive criteria that could help on selecting patients to be submitted to this technique. Methods: Fifteen patients with lateral compartment osteoarthritis and valgus deformity of the knee were submitted to distal femoral “V” varusing osteotomy fixated with lateral plate, pursuing knee alignment at 0° on the anatomical axis. The mean follow-up period was 81.4 months, ranging from 43 to 132 months. The Knee Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Direct comparison of the results of the present study with those reported above is not possible owing to distinct differences in the surgical methodologies employed. The surgical technique described in the present paper was different from those reported previously [1–7, 13, 30]. The apex of the V‐shaped osteotomy was proximal, in metaphyseal area, allowing greater contact area, stability and speed of healing.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Direct comparison of the results of the present study with those reported above is not possible owing to distinct differences in the surgical methodologies employed. The surgical technique described in the present paper was different from those reported previously [1–7, 13, 30]. The apex of the V‐shaped osteotomy was proximal, in metaphyseal area, allowing greater contact area, stability and speed of healing.…”
Section: Discussionmentioning
confidence: 85%
“…Success rates for DFO procedures, V‐shaped with distal apex, have been reported by a number of researches including Aglietti et al [2] (14 patients; 71.4 % success rate; mean follow‐up time 21.8 months) and Aglietti and Menchetti (17 patients; success rate 76.4 %; mean follow‐up time 108 months) [1]. In addition, Andrade et al [4] reported satisfactory results for 73 % of DFO patients who had been followed‐up for 81.4 months, and emphasized that there was no deterioration in the status of these individuals during the follow‐up. However, prospective comparative studies are needed to determine the best surgical option and its relation to the physical and functional outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation